2003
DOI: 10.5144/0256-4947.2003.158
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the “Triple Test” in the Diagnosis of Palpable Breast Masses in Saudi Females

Abstract: Background:For patients who present to clinicians with palpable breast lesions, the "triple test:" (physical examination, mammography and fine-needle aspiration cytology) can be employed to provide accurate diagnosis. In this study, the sensitivity, specificity and predictive values of triple test components were studied separately and in combination. Material and Methods: During the study period (from January 1998 to December 1999), 140 patients with palpable breast masses were subjected to all components of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 13 publications
0
14
0
2
Order By: Relevance
“…In a study done by Philip J Drew et al [12] , sensitivity of fine-needle aspiration cytology was 79.1% and specificity of 97%.the specificity is similar to our study. Al-Mulhim et al [13] , in a study to assess accuracy of the "triple test" found that fine-needle aspiration cytology (FNAC) showed 91.7% sensitivity, 100% specificity and 100% positive predictive value.…”
Section: Discussionmentioning
confidence: 99%
“…In a study done by Philip J Drew et al [12] , sensitivity of fine-needle aspiration cytology was 79.1% and specificity of 97%.the specificity is similar to our study. Al-Mulhim et al [13] , in a study to assess accuracy of the "triple test" found that fine-needle aspiration cytology (FNAC) showed 91.7% sensitivity, 100% specificity and 100% positive predictive value.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous reports that if the results of clinical assessment, mammography and FNAC are all combined, the accuracy of diagnosis reaches 100% 4 . Furthermore these techniques provide information on tumor size, number, extent and grade pre-operatively 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding economics, some studies have shown that the women treated in public institutions have more advanced stages of the disease, less access to modern therapies, and a lower survival rate than the patients treated in private institutions 43,44 . The triple test (physical examination, mammography, and cytology by fine needle aspiration) has been employed as a method to accurately diagnose palpable breast lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The triple test (physical examination, mammography, and cytology by fine needle aspiration) has been employed as a method to accurately diagnose palpable breast lesions. When the three diagnostic methods are consistent, the elimination of biopsy as a confirmatory test is usually recommended and can result in reduced spending 43 . In this context, artificial intelligence techniques, such as Bayesian networks using above characteristics, now represent a reality and may decrease the uncertainty present in biopsies derived from suspicious nodules, enabling the reduction of public health costs 43,44 .…”
Section: Discussionmentioning
confidence: 99%